Pengaruh Suplementasi Probiotik Bakteri Asam Laktat Terhadap Histomorfologi Usus Dan Performan Puyuh Jantan - Sapta Chandra Marnadi Hidayat; Sri Harimurti; Lies Mira yusiati (Faculty of Animal Science, Universitas Gadjah Mada, 2016)
The present study was conducted to investigate the effects of lactic acid bacteria (LAB) probiotics supplementation on intestinal histomorpholgy and performance of male quail. The LAB probiotics supplement contained of three strains, those are Lactobacillus murinus, Streptococcus thermophilus, and Pediococcus acidilactici. A total of 96 day-old male quails (DOQ) were randomly divided into four groups of LAB probiotic supplementation reared for 42 days. Oral supplementation of LAB probiotic were 0 (P0), 107(P1), 108 (P2), and 109(P3)CFU/mL/bird/day. Data were analyzed by analysis of variance CRD One-Way Anova continued with Duncan’s New Multiple Range Test (DMRT). The results showed that LAB probiotic treatment affected on the intestinal morphology, body weight gain, and feed conversion of male quail (P <0.05). Height of intestinal villi were 288.45±8.18, 322.72±1.84, 324.82±2.06, and 390.80±13.24 (µm) respectively. Width of intestinal villi were 112.82±2.35, 138.62±2.35, 162.57±17.15 and 130.72±13.45 (µm) respectively. Depth of intestinal crypts were 61.25±1.49, 72.50±6.25, 69.85±4.55, and 69.05±4.57 (µm) respectively. Feed intake were not different, but resulted difference body weight gain, which were 102.85±4.72, 109.20±4.13, 115.07±7.61, and 118.75±2.54 (g), respectively. Feed conversion were 4.30±0.43, 4.26±0.17, 3.91±0.30, and 3.79±0.27, respectively. This study indicated that supplementation of 109 CFU/mL/bird/day of LAB probiotics showed the best result.